APEC - agente pedagógico animado para o ensino de redes de computadores no mundo virtual - Freitas, Vania Cristina Bordin (2017)
The use of technological resources for education enables greater diversity in the assimilation of knowledge among students, through new learning methods such as virtual environments, virtual worlds, among others. However, it is fundamental that teachers seek to adapt these methods in the classroom, because when allying animated pedagogical agents and virtual worlds, perceives a greater pedagogical effectiveness, with motivational effects for students, due to the ability of these agents to express emotions. In this sense, in the course of this work the implementation of the Emotional Pedagogical Agent for Teaching Computer Networks (APEC), with emotional characteristics in the virtual world Teaching Computer Networks in a Free Immersive Virtual Environment (TCN5) was presented. APEC was modeled based on the OCC and Ekman models, with emotions that resulted in joy, happiness, relief, satisfaction, hope, deception and gratification, having audio interactions and textual chat, as well as having notions of the agent knowledge base Intelligent Agent adaptive to the Level of Expertise of Students (ELAI) about subjects related to networks security. The same does the recognition of the student and of his mood through sensors at the time of the selection of the emoticon. In order to verify the quality of the product, were carried out evaluations through questionnaires with specialists in computer networks (students of Post-Graduation in Computer Science, Federal University of Santa Maria), which were oriented the carry out the route of activities and make the tasks together with APEC. In this way, the results obtained were considered relevant to the research in relation to motivation, user experience and learning.